The Effectiveness of Chemotherapy in the Treatment of Patients with Breast Cancer - Feruza, Mahkamova (Central Asian Journal of Medical and Natural Science, 2022)
Chemotherapy is one of the main treatments for breast cancer. It involves the introduction into the body of drugs that destroy cancer cells and block their growth. In the first three stages, the technique is used in combination with a radical operation. At the fourth stage, radical operations are not performed, and chemotherapy becomes one of the main methods for controlling the tumor and its metastases.